ANALISIS SISTEM PEMBELAJARAN TILAWAH DAN TAHFIZH ALQURAN DI SEKOLAH DASAR SD PLUS JABAL RAHMAH MULIA MEDAN SUNGGAL - Awaluddin Awal (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2017)
Abstract: Elementary school SD Plus Jabal Rahmah Mulia is a school that excels in the field of Tilawahdan Tahfizh the The Holy Quran. With proven achievements students in memorizing the Holy Qurancontest branch on both the present district/municipality as well as the present province. This researchaims to know and describe the application of Tilawah dan Tahfizh the The Holy Quran method inincreasing the quality of memorizing the Holy Quran in the Subject of Memorizing the Holy Quran inthe students of SD Plus Jabal Rahmah Mulia, Medan, which included 1) planning the Holy Quranmemorization program at SD Plus Jabal Rahmah Mulia Medan, 2) planning Tilawah dan Tahfizh theThe Holy Quran method in the Subject of Memorizing the Holy Quran at SD Plus Jabal Rahmah MuliaMedan, 3) implementing Tilawah dan Tahfizh the The Holy Quran method in the Subject of Memorizingthe Holy Quran at SD Plus Jabal Rahmah Mulia Medan, and 4) evaluating the application ofTilawah dan Tahfizh the The Holy Quran method in the Subject of Memorizing the Holy Quran at SDPlus Jabal Rahmah Mulia Medan.